A world of water : rain, rivers and seas in Southeast Asian histories - Boomgaard, P., 1946-2017 (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde ;, 2007)
"Water, in its many guises, has always played a powerful role in shaping Southeast Asian histories, cultures, societies and economies. This volume, the rewritten results of an international workshop, with participants from eight countries, contains thirteen essays, representing a broad range of approaches to the study of Southeast Asia with water as the central theme. As it was exposed to the sea, the region was more accessible to outside political, economic and cultural influences than many landlocked areas. Easy access through sea routes also stimulated trade from an early age. However, the same easy access made Southeast Asia vulnerable to political control by strong outsiders. The sea is, moreover, a source of food, but also of many hazards. At the same time, Southeast Asian societies and cultures are confronted with and permeated by 'water from heaven' in the form of rain, flash floods, irrigation water, water in rivers, brooks and swaps, water-driven power plants, and pumped or piped water, in addition to water as a carrier of sewage and pollution. Finally, the volume deals with the role of water in classification systems, beliefs, myths, illness and healing"--Publisher's description